Effectiveness of 96% Ethanol Extract of Clove Leaves (Syzygium aromaticum (L.) Merr & Perry) as an Antibacterial Agent Against Staphylococcus epidermidis And Providencia stuartii - Listiana Masyita Dewi; Muhjatul Qolbi Nafi’ah (Magna Medika, 2022)
Background: The incidence of antibiotic resistance as a consequence of antibiotic abuse becomes a barrier in accessing effective care. The ability of bacteria to form biofilms is an internal factor that can prevent contact between bacteria and antibiotic agents, such as Staphylococcus epidermidis and Providencia stuartii. The use of plant extracts as an antibiotic is thought to be a promising solution. One of the plants that can be used as an antibiotic is the clove (Syzygium aromaticum (L.) Merr & Perry).